Refleksi Teologis Fenomena Manusia Menuju Kesempurnaan Iman - Damianus Suryo Pranoto; Armada Riyanto (Borneo Review, 2025)
This research aims to elaborate on the concept of the human person as a "pilgrim" constantly in dynamic growth and development. The primary focus is to understand how the transformation from an "old self" to a mature "new person," both physically and spiritually, can be realized in daily life. The identified problem is how individuals can actualize personal maturity that enables them to love others and overcome egoism, reflecting a willingness to self-sacrifice, much like the metaphor of a "dry leaf" enriching the soil for new growth. To achieve this, the study primarily employs qualitative methods through a philosophical-theological reflective approach and textual analysis of spiritual and existential concepts. Preliminary results indicate that personal maturity is expressed through spiritual maturity and humility, which motivate individuals to serve and love others, free from egoism. This implies that mature faith development is not merely about belief but also about behavioral transformation into socially and spiritually actualized individuals, for the collective good.